ANSWER
Vertical asymptote: x=-4
Horizontal asymptote: y=2
EXPLANATION
The given equation is
![f(x) = \frac{2x}{x + 4}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B2x%7D%7Bx%20%2B%204%7D%20)
The vertical asymptote is determined by equating the denominator to zero and solve for x.
![x + 4 = 0](https://tex.z-dn.net/?f=x%20%2B%204%20%3D%200)
The equation of the vertical asymptote is
![x = - 4](https://tex.z-dn.net/?f=x%20%3D%20%20-%204)
The numerator has the same degree as the denominator.
The equation of the horizontal asymptote is the coefficient of the leading term in the numerator expressed over the coefficient of the leading term in the denominator.
![y = \frac{2}{1}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B2%7D%7B1%7D%20)
y=2
Answer:
y=1/2x+3/2
Step-by-step explanation:
use the slope formula m=y2-y1/x2-x1 and get the slope. then plug in one set of points for y and x for (b)
Mikasa kills eren and Levi gets his legs broken and a scar on his eye and Sasha dies to a kid
Answer:
Your solution is (-3,0)
Step-by-step explanation:
Hi,
We know what Y is, so we can plug it into the second equation.
2x + y = -6
2x + (x + 3) = -6
Now, add the like terms...
3x + 3 = -6
3x = -9
x = -3
Now, plug x back in to find y.
y = x + 3
y = (-3) + 3
y = 0
Your solution is (-3,0)
Hope this helps :)